1994
DOI: 10.3171/jns.1994.80.6.1026
|View full text |Cite
|
Sign up to set email alerts
|

Combined approaches for resection of extensive glomus jugulare tumors

Abstract: Complete resection with conservation of cranial nerves is the primary goal of contemporary surgery for glomus jugulare tumors. This publication reports the value of combined surgical approaches in achieving this goal in 12 patients with extensive tumors. Eleven of these tumors were classified as Fisch Class C and/or D, while eight were categorized as Jackson-Glasscock Grade III or IV. Intracranial (intradural) extension was present in 10 patients; four patients had tumor extension into the clivus and two into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
1
7

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 73 publications
(15 reference statements)
5
117
1
7
Order By: Relevance
“…4 With the advent of improved microsurgical techniques and the use of combined approaches, the mortality rate has lowered substantially; however, cranial nerve injury continues to be a problem. [18][19][20][21] In a retrospective series of 176 patients treated between 1972 and 1998 and reported by Jackson, et al, 12 in 85% complete surgical control was described. The remaining 15% of their patients had a subtotal resection or recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 With the advent of improved microsurgical techniques and the use of combined approaches, the mortality rate has lowered substantially; however, cranial nerve injury continues to be a problem. [18][19][20][21] In a retrospective series of 176 patients treated between 1972 and 1998 and reported by Jackson, et al, 12 in 85% complete surgical control was described. The remaining 15% of their patients had a subtotal resection or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Patel, et al, 21 published their results in a series of 12 patients; they achieved complete resection in 10 of them by using combined approaches. These authors again demonstrated no surgically related deaths or episodes of stroke; however, three patients (33%) required facial nerve resection during the procedure, followed by nerve grafting.…”
Section: Neurosurg Focus / Volume 17 / August 2004mentioning
confidence: 99%
“…Complete resection of the tumor without damaging neighboring structures yields the best results. Modern technology with improvements in microsurgery can achieve good surgical results, with low mortality rates ranging from 0 to 5% in experienced hands [26,31,[37][38][39][40] . However, some surgically related cranial nerve [26] .…”
Section: A B Cmentioning
confidence: 99%
“…Because an opening of anastomoses that were not visible on preembolisation angiography sometimes occurs after embolization, a complete devitalization of the tumor cannot be expected. If embolization is done as the only treatment, it must be considered a palliative procedure [12,17].…”
Section: Discussionmentioning
confidence: 99%